Repercussões do treinamento resistido periodizado e destreinamento sobre o perfil funcional de mulheres idosas - Oliveira, João Carlos de (Universidade Federal de São Carlos, 2011)
Proposed in the middle 80's from the concepts of "classic" periodization sports training, the periodization of resistance training (PER) has become popular in recent years. The concept of the PER refers as planned and systematic variation of the volume and intensity of strength training (ST), although other acute variables of manipulated. The model consists of 3-4 phases of adaptation during a training program. Initially, the PER was developed to meet the need for enhancement of athlete performance. However, the PER has been used in different populations with very different goals than originally proposed. Thus, this is critical review of a literature, the challenge of understanding the PER not only as a variant or a component epistemological sports training, but as a strategy to affect the physiology as whole, with special attention in the elderly people. A total of 20 manuscripts were included this review. Six publications met the inclusion criteria. Altogether 179 subjects, men and women above 60 years were investigated. It was observed that the PER in the models linear (LP) or non-linear (UP) result in significant improvement in muscular strength capacity. The elderly of both genders were benefited to preservation of functional capacity, improvements in muscular function, and activities of daily living. However, it is not possible to determine which model of periodization is more efficient. Despite of increasing popularization of the PER, few studies have examined the effects of periodized training in the older adult. It takes more information about the comparative efficiency of different intensity and at different volumes in the periodization training approaches.
Keywords: Idosos; Exercícios físicos - aspectos fisiológicos; Promoção da saúde; Exercício resistido; Eletromiografia; Variabilidade da frequência cardíaca; Functional ability; Exercise program design, Physical fitness; CIENCIAS BIOLOGICAS::FISIOLOGIA